Carbon pricing and inflation expectations: Evidence from France - Jannik Hensel; Giacomo Mangiante; Luca Moretti (University of Zurich, Department of Economics, 2023)
This paper studies the impact of carbon pricing on firms' inflation expectations and discusses the potential implications for what constitutes the core of most central banks' mandate: price stability. Carbon policy shocks are identified from high-frequency changes in carbon futures price around regulatory events. The shock series is combined with French firm-level survey data. We document that a change in the price of carbon increases firms' inflation expectations. We then investigate how firms' business conditions are affected by carbon policy shocks and we find that firms' own expected and realized price growth respond similarly to inflation expectations. The effect on price expectations is more persistent than on actual price growth leading to positive forecast errors in the medium- /long-run. We also show that a sizable share of the increase in inflation expectations is due to indirect effects. Firms rely on their own business conditions to form expectations about the aggregate price dynamics. Therefore, the expected positive growth in their own prices significantly contributes to the observed increase in inflation expectations. Finally, we study how firms' responses are heterogeneously influenced by the shocks based on the share of input costs devoted to energy expenditures. We find that high energy-intensive firms tend to overreact relatively more in terms of their own price expectations compared to the actual price change the shocks induce.
Keywords: E31; E52; E58; Q43; Q54; 330; Climate policies; Carbon pricing; Inflation expectations; Monetary policy; Survey data